Keunggulan, Kendala, dan Pemanfaatan Pengembangan Bahan Ajar Tematik Terpadu Pada Pembelajaran PAI - Hudzaifah Hudzaifah; Rizal TamaOktavyan; Muhammad Iqbal; Anie Rohaeni (Jurnal Pendidikan Educandum, 2026)
This study aims to analyze the utilization of integrated thematic teaching material development in the school environment. The research employed a library research method with a descriptive qualitative approach. Data were collected through a systematic review of various national educational literature and journal articles relevant to the utilization of integrated thematic teaching material development. The findings indicate that the utilization of teaching material development based on an integrated thematic approach can be implemented through the foundations of the Qur'an and Sunnah in developing integrated thematic teaching materials for Islamic Religious Education (PAI), simple procedures for utilizing integrated thematic teaching material development, principles of integrated thematic teaching material development, as well as its advantages, challenges, and practical applications. The development and utilization of these teaching materials are based on principles that emphasize progressing from simple concepts to more complex ones, reinforcement through repetition in learning, and the provision of positive feedback. This study concludes that the utilization of integrated thematic teaching material development makes a significant contribution to character building, strengthening students' spiritual independence, and achieving balanced personality development among learners at both primary and secondary school levels.